2021
DOI: 10.1103/physrevphyseducres.17.020143
|View full text |Cite
|
Sign up to set email alerts
|

How perception of learning environment predicts male and female students’ grades and motivational outcomes in algebra-based introductory physics courses

Abstract: A recent paper used structural equation modeling to infer effects of gender-dependent student attitudes on several outcomes of introductory physics courses. The model used is precisely Markov equivalent to an equally plausible approximation in which a key gender-dependent coefficient in determining attitudes is indistinguishable from zero. I also argue that the qualitative framing may attribute to students motivations that actually belong to their teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 87 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…15,18 Additionally, in both algebrabased and calculus-based introductory physics courses, women have a lower sense of belonging than men even though the percent of women in algebra-based introductory physics is above 50%. 16,27,32 A student's belonging uncertainty has been less studied. In an introductory computer science course, it was seen that women had a higher belonging uncertainty than men and that higher uncertainty was correlated with their perceived potential ability.…”
Section: Social Belonging In General Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…15,18 Additionally, in both algebrabased and calculus-based introductory physics courses, women have a lower sense of belonging than men even though the percent of women in algebra-based introductory physics is above 50%. 16,27,32 A student's belonging uncertainty has been less studied. In an introductory computer science course, it was seen that women had a higher belonging uncertainty than men and that higher uncertainty was correlated with their perceived potential ability.…”
Section: Social Belonging In General Chemistrymentioning
confidence: 99%
“…However, affective benefits can be coupled with pedagogically effective strategies, such as engaging students in collaborative active learning, that simultaneously promote social belonging and content learning. , Generally, instructors can support students’ affective outcomes by promoting an inclusive classroom culture. ,, In a review by White et al describing inclusive and equitable practices in chemistry, the authors described the importance of the instructor mindset in creating an inclusive classroom culture and created a framework of equitable practices describing six categories including employing active learning and group work, fostering a sense of belonging, and validating students’ science identities. For example, the culture and environment of a STEM classroom set by an instructor’s practices and beliefs can influence students’ affective outcomes, including how students perceive themselves as scientists and science learners. , Thus, it is important for the instructor and instructional team to actively promote an inclusive culture within the classroom both through evidence-based pedagogical practices and explicit communication to students of the instructor’s belief in students’ ability to grow using effective study strategies (i.e., growth mindset). ,, To improve students’ science identity, instructors may incorporate diverse examples of successful scientists into their curriculum, including women, people of color, and chemists with diverse backgrounds and use diverse and inclusive examples, references, and analogies. While these evidence-based teaching practices have been shown to improve student retention and performance in the classroom, more research is needed to determine which current and new asset-based classroom practices directly affect students’ course-level social belonging, especially belonging uncertainty, and how these asset-based classroom practices affect students with differing identities, such as women in chemistry.…”
Section: Implications For Instructorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to perceived recognition, some studies have shown that students' interactions with peers and students' sense of belonging are also important aspects of their perceptions of the inclusiveness of the learning environment [6,[48][49][50][51][52][53][54][55][56]. For example, if students have a higher sense of belonging, they may approach others in the academic environment more often and with more positive attitudes, building better interactions with others and reporting higher perceived recognition from others [57].…”
Section: Background and Frameworkmentioning
confidence: 99%